(untitled) (Media Kesehatan Masyarakat Indonesia, 2019)
An anxiety is a feeling of worry associated with feelings of uncertainty or helplessness and an emotional conditions that is not yet clear about its specific object. Anxious conditionsoccurs a lot in pregnant women who have approached delivery period. This study aims to know influence of yoga prenatal gym to decreasing in anxiety of third trimester pregnant women in pattingalloang community health center and tamalate community health center makassar city. the type of research used included quasi experiment with a design that is the nonrandomized pretest posttest with control group design. This sample of study was 120 pregnant women that was divided 2 groups, namely group I (intervention group) for 60 pregnant women and group II (control group) for 60 pregnant women. Data analysis was univariate and bivariate analysis. The results showed a significant relationship between yoga prenatal gym intervention in reducing the incidence of anxiety in third trimester pregnant women in Pattingalloang Health Center and Tamalate Health Center Makassar City with a value of p=0,000. The conclusion of this study shows that yoga exercises at the prenatal stage have an influence on the decline in the incidence of anxiety of pregnant women.